Pelatihan Powerpoint dalam Pembelajaran pada POKJA TK/TP AL QUR’AN Tanjung Priok - Hendri, Hendri; Susanti, Melan; Saryoko, Andi; Khasanah, Nurul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Power Point is an application from Microsoft which is intended as a media presentation that functions to make it easier for users to organize the material to be delivered. Power point can make the audience better understand the presentation material being displayed. POKJA TK/TP AL QUR'AN is an educational forum that has not utilized Power Point facilities in its activities. In learning, the management of POKJA TK/TP AL QUR'AN experienced several obstacles, namely: they did not understand how to attract students' interest so that they could follow the learning process well and the limitations of the administrators of POKJA TK/TP AL QUR'AN in utilizing existing facilities on Microsoft Power Point, namely displaying videos or images that can support the delivery of material or teaching materials. This community service activity aims to apply and utilize Power Point in conveying the contents of learning materials. The methods used are the tutorial method, the question and answer method and the practice method directly using a laptop and a training module guide. The planned output targets for community service activities are publishing press releases in online media and activity videos as a form of publication and documentation of activities. The result of this activity is an increase in abilities and skills in delivering teaching materials so that they can help administrators and teaching staff of POKJA TK/TP AL Al Qur'an in attracting students' interest so they can follow the learning process.